Employed in the foodservice industry: likelihood of intervention with food safety threats. Issue 2 (12th October 2020) - DiPietro, Robin B.; Harris, Kimberly; Jin, Dan
Abstract : Purpose: The purpose of this study was to investigate restaurant employee behaviors and their likelihood of intervening when witnessing food safety threats. Design/methodology/approach: A mixed method was used for this study with the focus group interview and survey questionnaire. A total of eight focus groups ranging in number of participants from to 6 to 12 were asked to respond to presented scenarios that depicted restaurant employees committing food safety risk behaviors and threats in the restaurant environment that would present food safety risks such as out-of-stock bathroom supplies, dirty tables in the restaurant dining area, employee personal hygiene issues and unclean production equipment. These participants were also asked to complete a draft of the survey that would later be edited and distributed to the sample population. Findings: Results suggest that social norms and perceived severity of threats impact the likelihood that restaurant employees will intervene. Implications for academics and practitioners are discussed. Originality/value: This study was special as it provides a synthetic viewpoint that considers how service organizations can work to do a better job of interviewing employees before starting their jobs about their beliefs and personal practices of food safety at home, their previous work in the restaurant industry and food safety culture that they may have worked in before, as well as increasing the communication in restaurants to build a food safety culture. These practices can help to lower risks to the public regarding food safety and can help to build relationship trust in the brands that we all love to indulge in when dining out.